MicroRNA-1985 enhances the redox capability of scallop (Patinopecten yessoensis) in response to poly(I:C) stimulation by targeting MNK1 - Yu, Linghui; Deng, Huiqi; Liu, Shaohua; Xia, Jianpin; Hao, Zhenlin; Yin, Donghong; Zhan, Yaoyao; Chang, Yaqing (Frontiers in Immunology, 2025)
To clarify the microRNA (miRNA)-target gene axis is involved in response to pathogen-associated molecular pattern (PAMP)-induced oxidative stress in shellfish, the full-length cDNA of a novel mitogen-activated protein kinase-interacting kinase 1 (MNK1) homolog gene from the scallop Patinopecten yessoensis (PyMNK1) was cloned and characterized. The interaction between miR-1985 and PyMNK1 was verified, and then the responses and possible molecular function of miR-1985, PyMNK1, and miR-1985/PyMNK1 axis to poly(I:C) (a classic virus-related PAMP) stimulation in P. yessoensis were explored and preliminarily dissected. The results indicate: 1) The full-length cDNA of PyMNK1 was 5354 bp, with a high level of sequence conservation across mollusks. 2) MiR-1985 bound to the 3’-UTR of PyMNK1 and negatively regulated the expression of PyMNK1. 3) PyMNK1 may repress the relative expression of superoxide dismutase (SOD) by binding its promoter. 4) Both PyMNK1 silencing and miR-1985 overexpression promoted the expression and enzymatic activity of SOD. 5) The miR-1985/PyMNK1 axis may be involved in the response to poly(I:C) stimulation by elevating the activity of the SOD/catalase axis. To summarize, all observations from this study indicated that P. yessoensis may enhance its redox capability via the miR-1985/PyMNK1/SOD/CAT cascade and thereby alleviate PAMP-induced oxidative stress.